The hybrid model of attentional control: New insights into hemispheric asymmetries inferred from TMS research. (July 2015) - Duecker, Felix; Sack, Alexander T.
Abstract: Several competing theories on the mechanisms underlying attentional control have emerged over the years that, despite their substantial differences, all emphasize the importance of hemispheric asymmetries. Transcranial magnetic stimulation (TMS) has proven particularly successful in teasing them apart by selective perturbation of the dorsal and ventral fronto-parietal network. We here critically review the TMS literature and show that hemispheric asymmetries within the dorsal attention network differ between parietal and frontal cortex. Specifically, posterior parietal cortex seems to be characterized by a contralateral bias of each hemisphere and competition between them. In contrast, the right frontal eye field seems to be involved in shifting attention toward both hemifields, whereas left frontal eye field is only involved on shifting attention toward the contralateral hemifield. In the light of presented evidence, we propose to revise the functional-anatomical model originally proposed byCorbetta and Shulman (2011, 2002 ) and introduce a hybrid model of hemispheric asymmetries in attentional control. Highlights: Three competing theories propose hemispheric asymmetries in attentional control. We review TMS research to differentiate between these theories. All theories capture relevant aspects of attentional control. Hemispheric asymmetries differ between parietal and frontal cortex. We propose a hybrid model of hemispheric asymmetries in attentional control.